Teachers' Technological Pedagogical Content Knowledge (TPACK) Implementation in English for Specific Purposes (ESP) Classrooms at Vocational High School - Desi Ramadali Hutauruk; Ahmad Amin Dalimunte; Rahmah Fithriani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to examine the implementation of Technological Pedagogical Content Knowledge (TPACK) by English teachers in ESP instruction within the tourism program at a vocational high school, using a descriptive qualitative approach with a phenomenological design involving two English teachers (T1 and T2) selected through purposive sampling, with data collected through classroom observations, semi-structured interviews, and documentation, then analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, further enriched by the SAMR model and the Technology Integration Matrix (TIM) as complementary analytical frameworks. The findings reveal that both teachers successfully integrated all seven components of TPACK in a contextually appropriate manner, albeit through distinct technological configurations, with T1 utilizing authentic videos and Instagram to reach the Redefinition level within the SAMR model, while T2 optimized the use of PowerPoint and Blooket to reach the Modification level, and both teachers further succeeded in establishing active, collaborative, and authentic learning environments, as evidenced by the TIM analysis. These findings lead this study to conclude that the successful implementation of TPACK is determined not by the sophistication of the technology employed, but by teachers' capacity to contextually align technology, pedagogy, and content in accordance with the demands of the learning environment.